Salmonella sp Group A: A rare cause of bacterascites. A case report - Gustavo López-Arce; Aldo Torre-Delgadillo; Félix I. Téllez-Ávila (Annals of Hepatology, 2008)
Bacterascites (BA) is a minimally studied and defined entity. Its prognosis and clinical course are not well defined, and currently there are no management guidelines. We present a rare cause of BA in which Salmonella sp group A was isolated in a 44 year old man with cirrhosis who had diarrhea and fever three days earlier. Treatment with intravenous ceftriaxone was effective.